Ciclos político econômicos : um teste para os clubes de futebol - Recena, Inácio Gaudie Ley (2015)
This work, by addressing the theories of Political and Economic Cycles and financial elements balances available in the sample Football Clubs, aims to find the influence of political cycles in the financial relationship of the teams between the period 2007-2013. In this dissertation the following theories are presented: Traditional Opportunist, Traditional Partisan, Rational Partisan and Rational Opportunist. After collecting the financial data and comparative analysis, its relation with the theories was established by the Econometric Method Panels Data, in which the dependent variable determined, was the expense being held the Hausmann test, which indicated the Method of Fixed Effects to the most suitable for the model results. The found results affirm the positive relationship between the dependent variable, Expense, the variable, Income and the variable of political cycles of three years, which indicates that clubs that have elections every three years have a greater influence in expenses of the clubs lack political cycle. The study itself deepens critical thinking about the situation of Brazilian Football and opens possibilities for new confrontations both theoretical as practical on the variables which influence in sport management's behavior mainly in Brazil and consequently the quality of it compared to worldwide Football.